Andrés Rivera: horizontes históricos para una izquierda derrotada - Ivan Jimenez (Cuadernos LIRICO)
Through the motif of historical horizons, a persistent gesture in Rivera’s work is examined: the writing of fiction concerned with the history of the nineteenth century in a later moment defined by the coincidence of the crisis of Marxism and the increase of memory expressions (Traverso). From family memories of anti-Semitism and anticommunism through postcolonial consideration of the history of Argentina, United Kingdom and France, a “losing and resisting” tradition is quitely traced, shaped with revolutionaries who lose their fights against the vanquishers.  In this imaginary work, historic references interact with literary traditions, which are invoked to let us hear the whispers of the dead. By the side of the specter of Marx, appears, thinly veiled, the specter of Shakespeare, so that beyond social and deterministic realism, fiction adopts a theatricality which renders visible the recurrences of history.